PENGARUH DER DAN EPS TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BAVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Sutisna Arisandi; Gista Rismayani; Yeni Fitriani Somantri; Verra Rosyalia Widia Sofyan (Jurnal Akuntansi dan Bisnis (AKUNTANSI), 2026)
The purpose of this research is to examine the relationship between influence of debt to equity ratio, earnings per share on stock returns. This thesis uses a quantitative approach with a sample of 10 companies from the food and beverage sector listed on the Indonesia Stock Exchange for the 2019-2023 period, taken using a purposive sampling technique. The data was collected over a 5 year period, resulting in a total of 50 financial reports being observed. Based on partial test results, the debt to equity ratio (X1) variable has a regression coefficient of 0.220 with an error rate of 5% (0.220>0.05), indicating that investment decisions have an insignificant effect on stock returns. The earnings per share variable (X2) has a regression coefficient of 0.707 with an error rate of 5% (0.707>0.05) indicating that earnings per share has no significant effect on stock.